GAS-CHROMATOGRAPHY ASSESSMENTS OF THE MAJOR VOLATILE COMPOUNDS IN TRADITIONAL FRUIT BRANDIES THROUGHOUT FRUIT AND WOOD MATURATION - DIPPONG, Thomas; AVRAM, Alexandra; MIHALI, Cristina (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Traditional home-made plum and apple brandies were analysed aiming to assess the main physico-chemical characteristics including density, ethanol content, total acidity, total extract, total sulphur dioxide (SO2) and refractive indices. The major volatile compounds, such as, methanol, linear superior alcohols (propan-1-ol, butan-1-ol, butan-2-ol), branched superior alcohols (2-methylpropan-1-ol and 3-methylbutan-1-ol) and also ethyl acetate, acetaldehyde and acetal compounds, were assessed using gas chromatography coupled with flame ionization detector (GC-FID). The technology of incorporating fruit (cherries and pears) or wood (mulberry and poplar) in the brandy was presented along with the influence of their addition on the composition of the plum and apple brandies and on their physico-chemical characteristics. The changes in the composition of plum and apple brandies throughout 4 weeks of maturation process in the presence of wood or fruit, showed an increase in density, acidity and total extract and decrease in the concentration of ethanol, total sulphur dioxide (SO2) and acetaldehydes. The addition of mulberry and poplar wood in the brandies decreased the concentration of acetaldehyde. The addition of both fruits significantly increased the concentration of ethyl acetate.